Menjelajahi Peran Kemampuan Dinamis dalam Meningkatkan Kebaruan Produk Baru: Fokus pada Sensing, Seizing, dan Resource Reconfiguration - Septian Wahyudi; Syafaruddin Z (Pelantar Press, 2024)
Dynamic capability encompassing sensing, seizing, and reconfiguring, are key to product innovation, especially for Village-Owned Enterprises (BUMDesa) in Indonesia. Nevertheless, the literature on the use of these capabilities in rural business contexts is scarce. This research purpose to find out how these three capabilities are useful for BUMDesa in plugging product novelty. Data collection and analysis had a quantitative approach to demonstrate the impact of each capability. The results suggest that sensing and reconfiguring are key components of product novelty, while the effect of seizing is insignificant. The strategy of sensing encourages BUMDesa to know market opportunities and threats, while reconfiguring gives flexibility to the organization and the adoption of a new technology that support input for innovation. On the other hand, the captures had less effect because of limited resources and the idealism of BUMDesa with practical local solutions. Sensing and reconfiguring are imperative in the support of product innovation in BUMDesa, while seizing strategies may require some adjustment to soconditions. The present research adds a new perspective on the dynamic capabilities of rural enterprises by assessing product novelty and its impact on rural enterprise development.